Analysis of Challenges in Digital Literacy Development in MSME Actors in Bogor Regency - Pratiwi, Aprilianti; Kaligis, Retor A.W.; Putra, Riza Darma (EKSPRESI DAN PERSEPSI : JURNAL ILMU KOMUNIKASI, 2025)
As a contributor to the country's foreign exchange and job openings for the Indonesian people, it is appropriate for MSMEs to be one of the priorities in government programs. The government has made many efforts to empower MSMEs, including through Government Regulation (PP) Number 7 of 2021 concerning the Facilitation, Protection, and Empowerment of MSME Cooperatives. Previous research explains that higher education empowers MSMEs by conducting several community service programs for MSME actors. This research aims to dig deeper into the digital literacy owned by the Teras Ciapus MSME Community members in Bogor Regency and their challenges in improving digital literacy. Focus Group Discussions and in- depth interviews use qualitative methods in this study. The FGD was conducted for 63 active members of the Ciapus Terrace community. S The measurement standard used in this FGD activity is to identify the experience of members of the Ciapus Core Community in using digital marketing. An in-depth interview was conducted with the chairman and four Teras Ciapus MSME Community members. The results of the study found that there is still a low level of digital literacy owned by members of the Ciapus Teras community. All community members have digital devices, such as smartphones, but have not used them optimally. Several challenges they face include social and cultural barriers, lack of awareness of ICT use, and unequal opportunities for members to participate in digital training activities. The results of this research hope to provide strategic input for the government, non-governmental organizations, and other stakeholders in supporting the development of MSMEs through strengthening digital literacy.